Stitching with a handful of beads : necklaces, bracelets, earring, pendants, rings - Cave, Carolyn (Kalmbach Books, 2017)
Bead stitchers at every level appreciate fresh, new projects that use the beads and materials they already know and love. Stitching with a Handful of Beads offers 30 projects that use just 3-5 types of beads to create beautiful finished jewelry. The book opens with a Basics section outlining the stitches used in the book, and contains six project chapters organized by jewelry type: earrings, rings, bracelets, ropes, pendants, and necklaces. The projects use seed beads, pearls, crystals, and shaped beads -- stitchers' perennial favorite beads, and those most commonly found in stores. Every project includes easy-to-follow instructions in designer Carolyn Cave's signature style, plus complete, clear illustrations that make construction a breeze. Many of the 30 projects include easy design variations, making the book a great value. Projects stitch up easily, and are ideal for experienced stitchers wanting to make quick gifts, or beginning stitchers looking for rewarding projects that are easy to complete. Offers step-by-step instructions for stitched jewelry projects that showcase two-hole seed beads, including bracelets, rings, earrings, ropes, and pendants.